2016
DOI: 10.1016/j.ajpath.2016.08.020
|View full text |Cite
|
Sign up to set email alerts
|

Hypophysitis Secondary to Cytotoxic T-Lymphocyte–Associated Protein 4 Blockade

Abstract: Hypophysitis that develops in cancer patients treated with monoclonal antibodies blocking cytotoxic T-lymphocyte-associated protein 4 (CTLA-4; an inhibitory molecule classically expressed on T cells) is now reported at an incidence of approximately 10%. Its pathogenesis is unknown, in part because no pathologic examination of the pituitary gland has been reported to date. We analyzed at autopsy the pituitary glands of six cancer patients treated with CTLA-4 blockade, one with clinical and pathologic evidence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
298
3
7

Year Published

2017
2017
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 330 publications
(318 citation statements)
references
References 33 publications
10
298
3
7
Order By: Relevance
“…Higher expression of CTLA-4 in the pituitary gland was reported to be related to hypophysitis, due to type II or type IV allergy by IgG1 or IgG2 type anti-CTLA-4 antibodies [18] . Yamauchi, et al reported that PD-L1 and PD-L2 expressions on thyroid gland might be related to nivolumab-induced thyroiditis [52] .…”
Section: Other Possible Mechanisms In Endocrine Iraesmentioning
confidence: 99%
See 2 more Smart Citations
“…Higher expression of CTLA-4 in the pituitary gland was reported to be related to hypophysitis, due to type II or type IV allergy by IgG1 or IgG2 type anti-CTLA-4 antibodies [18] . Yamauchi, et al reported that PD-L1 and PD-L2 expressions on thyroid gland might be related to nivolumab-induced thyroiditis [52] .…”
Section: Other Possible Mechanisms In Endocrine Iraesmentioning
confidence: 99%
“…Most of hypophysitis related to irAE is induced by anti-CTLA-4 antibody, and anti-PD-1 antibodyinduced hypophysitis is less common (<1.0%) [4,18] . Hypophysitis related to irAE occurs more often in men than women [15,16] .…”
Section: Hypophysitis Related To Iraementioning
confidence: 99%
See 1 more Smart Citation
“…AH can be fatal if the adrenal insufficiency is unrecognized23, so that some cases are still reported at autopsy4 (see Table 1 in ref. 4).…”
mentioning
confidence: 99%
“…CTLA-4 antigen was expressed by pituitary endocrine cells with the highest levels found in patients with severe hypophysitis. In patients with severe hypophysitis, immune reactions induced aggressive necrotizing form with extensive destruction of the adenohypophyseal architecture (51). Pituitary autoantiboides against thyrotrophs, corticotrophs and gonadotrophs were identified in the sera of patients who developed hypophysitis (52).…”
Section: Secondary Hypophysitismentioning
confidence: 99%